Anesthetic management of a large mediastinal mass for tracheal stent placement - Rajagopalan,Suman (2016)
ABSTRACT The anesthetic management of patients with large mediastinal masses can be complicated due to the pressure effects of the mass on the airway or major vessels. We present the successful anesthetic management of a 64-year-old female with a large mediastinal mass that encroached on the great vessels and compressed the trachea. A tracheal stent was placed to relieve the tracheal compression under general anesthesia. Spontaneous ventilation was maintained during the perioperative period with the use of a classic laryngeal mask airway. We discuss the utility of laryngeal mask airway for anesthetic management of tracheal stenting in patients with mediastinal masses.